Fit and forecasting Indonesia banking stock price during Covid-19 pandemic based on logistic differential equation system - Noviantri, Viska; Chandra, Andree Sulistio; Yuhani, Yusof (Association for Computing Machinery, 2023)
Banks are financial service companies that play an important role in channeling finances to folks who want capital for micro, small and medium establishments. The increase in bankrupt companiesand unemployment in many sectors due to the uncertain condition during the Covid-19 pandemic will affect bank performancewhich may change their stock price dynamics. This study analyzes the stock price fluctuation in banking companies using a logistic differential equation model since the fluctuation changes rapidlyand has a nonlinear pattern. This model was finished by the fit and forecasting process; and completed by Mean Average PercentageError (MAPE) value to see how well the model captures the stock price fluctuation. Furthermore, the closing stock price during the pandemic of the four banks with the largest number of assets in Indonesia’s banking sectors is applied here to complete the fit and forecasting simulation. The results show that the MAPE average value of this model in the fit process is 6.331%. In other words, the logistic equation accurately represents banking stock price fluctuation. Next, the forecast process conducts to predict the stock price fluctuation for some periods. Thus, the fluctuation of stock prices in Indonesian banking during the Covid-19 pandemic can analyze further.